Pendayagunaan Zakat Produktif Untuk Meningkaatkan Sarana dan Prasarana Pendidikan di LAZIS UII (Lembaga Amil Zakat Infaq dan Sedekah Universitas Islam Indonesia) - Afief Mubayyin; Nurjanna (Qolamuna : Jurnal Studi Islam, 2023)
One of the biggest problems in Indonesia is related to the lack of qualified education. In fact, the educational fund from government (locally called BOS or school operational aid) and government aid have not sufficiently improved the education quality in this country. With the majority of Moslem population in Indonesia, zakat in turn can offer an opportunity to participate in improving the quality of educational facilities and infrastructures - particularly in Yogyakarta. LAZIS UII is an institution established based on the idea of the previous rector purposely to develop the zakat. As UII is a university, then LAZIS UII has a broader focus to be involved in educational sector in which the zakat fund will annually be allocated to improve the educational facilities and infrastructures in Yogyakarta. The aim of this research was to observe how the mechanism of zakat fund allocation done by LAZIS UII to improve the educational facilities and infrastructures. It is found out that LAZIS UII focuses on improving the educational facilities and infrastructures in the form of scholarship and allowances given for the teachers in private Islamic Schools (MI) and school renovations. All forms of fund allocation done by LAZIS UII has been in accordance with the Islamic economic perspective. Keywords: Zakat Fund, Education, Facilities and Infrastructure